The war comes to Porto: considerations about the impacts of the invasions of the city of Porto during the Napoleonic Wars - Couceiro, Pedro (2018)
The invasions that Portugal suffered, by the Napoleonic armies in early 19th century correspond to the beginning of a period of great changes in the Portuguese society. Understood as a specific phenomenon, they are the result of political and ideological circumstances that took place at a European scale. The fact is that the French intervention, beyond the strictly military aspects, produced a series of national and local impacts with undeniable consequences in the ideological evolution at the political, social and economic levels. The Portuguese territory felt deeply the negative impact of these military interventions that were only able to control a few parts of the country and its power structures. Among the busiest seaports, the city of Porto was a prime target for the achievement of French plans, given its geographical location and due to its recognized political and economic role. The traditional sources used to study these events describe, with a patriotic rhetoric and a denunciative discourse, a whole series of economic and social constraints as well as the several abuses perpetrated by the French troops that occupied the city. It became necessary for the French to find place for the instalment and supply of the troops, as well as to restore order and the normal urban services. Besides, the spaces under military occupation tended to be the scenery of animosities among citizens and invaders, not only because they were enemies, but also because of the difficulties of life under a state of war. The same reports confirm the increase of the phenomenon of marginality and poverty that demanded quick answers from the city‘s social institutions.